Siskopatuh as a Government Public Relations Strategy - Past Novel Larasaty; Riska Afriyanti (JKG (Jurnal Komunikasi Global), 2020)
Following various issues regarding malpractices and frauds done by irresponsible Umrah and Hajj Organiser Companies (PPIU) in Indonesia, the Indonesian Ministry of Religious Affairs (Kemenag), is assigned with a more significant challenge to overcome the problem that causes billion rupiah loss on the side of the customer (jamaah). One of the efforts tried to be implemented is by creating Integrated Computerised Management for Umrah and Special Hajj, also known as SISKOPATUH as the channel to register, monitor and control the flow of Umrah and Hajj application and process for both jamaah and PPIU. This research drew attention on how Kemenag has tried to socialise and implement SISKOPATUH that they have planned to be the protector of jamaah.  In-depth interviews were done with stakeholders of Umrah and Hajj organisers; two from government and three from private sectors. The findings reveal that a number of strategies were used by Kemenag to communicate their programme to protect the people from Umrah and Hajj malpractices.